The recovery methods effect on blood lactates following 100 meters male sprinter training in SMK Putera, Kelantan / Fariza Syafiqah Mohamad - Mohamad, Fariza Syafiqah (Faculty of Sport Science and Recreation, 2016)
The aims of this study is to determine the recovery methods effect on blood lactates following 100 meters (100 m) male sprinter training in SMK PUTERA, Kelantan. The recovery methods tested consist of 10 minutes (min) of active cool down, 10 min of cold bath (10 to 15°C), and also 10 min of contrast bath (cold: 7.22 to 22 °C; hot: 26.67 to 45°C) recovery method. For every recovery session, blood lactates level will be taken pre and post to recovery session in order to gain the rate of reduction that occurs. Nine (n=9) 100 m male sprinters from SMK PUTERA, Kelantan were recruited by using purposive sampling technique. It is hypothesized that there is no different between blood lactates rate of reduction between all three recovery methods used. The result meanwhile showed that there was a significant different between the recovery methods effect on male SMK PUTERA sprinters in Kelantan. In conclusion, contrast bath have the highest rate of reduction of blood lactates compared to cold bath while active cool down shows a rate of addition in blood lactates level.